ANALISIS MANAJEMEN RISIKO TERHADAP PENGGUNAAN E-BANKING (MOBILE BANKING DAN INTERNET BANKING) PADA BANK BNI SYARIAH - Hotnaida Siregar; Juharati Dinia; Retno Septiani (Universitas Muhammadiyah Tangerang, 2021)
E-banking is an application that launches banks in order to improve operational activities with a variety of financial and non financial transactions. One of the banks that launches Electronic transactions is BNI Syariah bank. E-banking is a twenty-four-hour banking service provided for finance to be able to conduct banking transactions through mobile phones connected to the internet. E-banking at BNI Syariah Bank. As background research because there is an increase in the use of electronic transactions at the time of this pandemic. The ease of use of e-banking can be put aside by some people to reduce, lie and break into savings funds. This research is a literature study conducted by collecting data through the annual report book and BNI Syariah website by reading, recording and managing data so that it gets results. The data collection is done at secondary data sources which are then analyzed by qualitative descriptive methods. The results show that BNI Syariah carries out risk management on the use of electronic transactions by following Bank Indonesia Regulation No. 13/23 / PBI / 2011 concerning the Implementation of Risk Management for Sharia Commercial Banks and Sharia Business Units. In addition, to avoid risk, BNI Syariah provides tips on safe tips, requirements, how to register in accordance with procedures, and also limits transactions in the use of E-banking to avoid fraud, requiring use and problems of use.Keyword: BNI Syariah E-banking